The Hypertextual Process of Rewriting a Plurimedial Work: Joan Fuster and Vicent Garcés’ Ballet Marinada - Xavier Hernàndez i Garcia (Interlitteraria)
Joan Fuster is one of the most prolific and influential authors in Catalan culture. In 1953, the Valencian composer Vicent Garcés contacted Fuster to ask for his collaboration in writing a “Valencian opera”. Although this project will never come to fruition, it will lay the foundations of a friendship that will crystallise in Fuster’s only literary collaboration on a musical composition: the symphonic ballet Marinada, which was written in the late 1940s, during a stay of Garcés’ in Paris and premiered in València in 1957. The original lyrics, written by Garcés himself, were inspired by Valencian folk songs. Fuster’s intervention was decisive in providing the necessary literary quality that the work needed in order to win the 16th Joan Senent Ibañez award in 1972 and to have a greater diffusion. In this article, we intend, from a hypertextual perspective, to study the mechanisms that Fuster used in the process of rewriting Garcés’ text to turn a minor work into a composition recognised both musically and literarily. The correspondence between Garcés and Fuster and the analysis of the original scores and other work documents found in Fuster’s archive will allow us to describe the process of rewriting using an intermedial approach, as we will study a work that combines two media, i.e. music and literature.